Digital twins-based flexible operating of open architecture production line for individualized manufacturing. (August 2022) - Leng, Jiewu; Chen, Ziying; Sha, Weinan; Lin, Zisheng; Lin, Jun; Liu, Qiang
Highlights: Digital twins-based flexible operating of open architecture production line. The reconfigurability based on open architectural architecting of cyber system and physical system. Integration of online system-level logistics simulation and equipment-level multi-physical field simulation. Abstract: Individualized manufacturing implies high flexibility of both the hardware and software of the production lines based on a fast physical and logical system (de)commissioning. This paper proposes an open architecture production line (OAPL) design together with a digital twins-based flexible operating approach for individualized manufacturing. Firstly, an OAPL is designed and implemented with physical reconfigurability by orchestrating different open architectural platforms together with open architecture machine tools (OAMTs). Secondly, an open architectural style modeling and configuration method is presented to enable the software reconfigurability of the controls of the OAPL. Thirdly, a digital twin-based online process emulating and multi-physics simulation is integrated to aid the comprehensive characterizing of the operation status of the OAPL. Based on the system reconfigurability and digital twins system, a triple-layer Learning-Optimization-Reacting approach together with an ensemble algorithm for flexible operating of the OAPL is proposed. The digital twins are formed with the ability to flexibly operate the OAPL for catering to different individualized requirements. A demonstrative implementation of a stepping-motor assembly OAPL is presented finally.